6x+3(3)=24

Simple and best practice solution for 6x+3(3)=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3(3)=24 equation:


Simplifying
6x + 3(3) = 24

Multiply 3 * 3
6x + 9 = 24

Reorder the terms:
9 + 6x = 24

Solving
9 + 6x = 24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 6x = 24 + -9

Combine like terms: 9 + -9 = 0
0 + 6x = 24 + -9
6x = 24 + -9

Combine like terms: 24 + -9 = 15
6x = 15

Divide each side by '6'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| x+139=-3x-9 | | 4x^2+8x-52=-3 | | =15M-850N+0.4M^2+22P | | -7x-4=x-188 | | -7x-4=a-188 | | =20H+2.4H^2-0.01H^3 | | 6x+3(2)=24 | | =75b+200 | | 7(5a+9)+5(2+a)= | | X^2-21x+90= | | 10x^3(3x+6xy)= | | 2=2(x+4)-4(x-1) | | =75b-200 | | A^2-21a+90= | | 3x^2+33x= | | sin^2(x)=tan(x) | | 15c=56.70 | | 56.70+c=20 | | 4x^2+25y^2+16x-50y-59=0 | | 56.70c=15 | | f(x)=3x^2+12x-12 | | 2x^2-30x= | | Y=2(x+4)-4(x-1) | | 14n^2-28n= | | c/15=56.70 | | log(x)=2.4 | | 2r^2+8r-3=-9 | | 4x^2-16x-9y^2+18y+6=0 | | 4y-12=-36 | | 3y^2+4y+4=8 | | 7.5x=65+x | | (6w-3v-1)(4w+3)= |

Equations solver categories